Differential received signal strength based RFID positioning for construction equipment tracking. (October 2019) - Wu, Changzhi; Wang, Xiangyu; Chen, Mengcheng; Kim, Mi Jeong
Abstract: A novel differential received signal strength (RSS) positioning algorithm is proposed in the paper. Different from traditional methods to find the relationship between RSS and distance, this new positioning approach is based on linear regression of angle and differential received signal strengths. The advantages of this positioning algorithm is robust to heterogeneity of RFID tags as well as direction between tag and reader. Several experiments are firstly carried out in open environment and then a further experiment is conducted in a LNG training centre to validate our proposed algorithm. The results show that our proposed algorithm can achieve better accuracy than existing RFID positioning approaches for equipment tracking.